Pengenalan Huruf Untuk Meningkatkan Ketrampilan Membaca Dengan Animasi Picture Kelas 1 SDN 65 Kota Ternate - jamal, agus hi (Jurnal Ilmiah Wahana Pendidikan, 2023)
National education functions to develop abilities andforming a dignified national character and civilization in order to make the nation's life more intelligent, aimed at developing the potential of students so that they become human beings who believe and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become citizens who democratic and responsible.The method used is classroom action research, namely research carried out in the classroom with the aim of improving or increasing the quality of learning practices. This class research method was carried out on reading learning using animated picture media to improve students' reading learning on the subject of reading in Indonesian language lessons.This research was carried out in class I of SD Negeri 65 Ternate City. With a total of 20 students consisting of 8 male students and 12 female students. This research was conducted to improve reading skills with animated pictures with the aim of increasing students' creativity which was carried out in two learning cycles.